The evaluation of online strategies on Malaysian women-related web sites - Abdul Hamid, Norsiah (2005)
Electronic commerce via the Internet offers a new paradigm for doing business. Hence, the creation and development of its content is not a one-time effort.The fast speed of technological innovation in the web site design and the increasing competitiveness of the medium require all marketers to continually enhance their web sites.This paper is about the effectiveness of the local women web sites.It aims to study the online strategies being used by Malaysian women-related web sites in order to get involved with the new type of offerings and transactions over the Net.It also aims to study the pattern of different companies whether they achieved the same performance for their E-Commerce.The survey was adapted from Bell and Tang (1998) in order to evaluate the online activities.Results show that some sectors scored higher in certain aspects while some other sectors scored lower.Furthermore, there are companies that still lacked in certain aspects and need improvement.Overall, companies are trying their best to provide users with the most informative and attractive web sites.